2022
DOI: 10.3389/fgene.2022.887542
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of a 6-Ferroptosis Related Gene Signature for Prognosis and Immune Landscape Prediction in Melanoma

Abstract: Ferroptosis is a newly discovered form of non-apoptotic cell death that relies on iron-mediated oxidative damage, playing a crucial role in the progression and therapy resistance of melanoma. Hence, the potential value of ferroptosis-related genes (FRGs) as a prognostic model and therapeutic target in melanoma requires further investigation. In this study, the relationship between FRGs and melanoma was revealed by analyzing the mRNA expression profiles from The Cancer Genome Atlas (TCGA) and Gene Expression Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Zeng et al developed a prognostic model depending on the expression of two FRGs (ALOX5, CHAC1), and differences in the underlying diseases of SKCM did not effect on the expression features of these two genes (Zeng et al, 2021). Additionally, studies showed five-, six-, eight-, nine-and ten-FRG predictive models according to Frontiers in Genetics frontiersin.org the RNA sequencing data have been constructed (Xu Z et al, 2021;Xu and Chen, 2021;Chen et al, 2022;Ping et al, 2022;Yue et al, 2022). These models forecasted the melanoma patients' prognosis and exhibited the close relationship between immune function and FRGs.…”
Section: Discussionmentioning
confidence: 99%
“…Zeng et al developed a prognostic model depending on the expression of two FRGs (ALOX5, CHAC1), and differences in the underlying diseases of SKCM did not effect on the expression features of these two genes (Zeng et al, 2021). Additionally, studies showed five-, six-, eight-, nine-and ten-FRG predictive models according to Frontiers in Genetics frontiersin.org the RNA sequencing data have been constructed (Xu Z et al, 2021;Xu and Chen, 2021;Chen et al, 2022;Ping et al, 2022;Yue et al, 2022). These models forecasted the melanoma patients' prognosis and exhibited the close relationship between immune function and FRGs.…”
Section: Discussionmentioning
confidence: 99%
“…The endoplasmic reticulum stress-related model comprises seven ERSRGs, including PDX1, IGFBP1, DDIT4, PPP1R3G, CFTR, DERL3 and NUPR1. Researchers have found that model genes are closely associated with both carcinogenesis and anti-tumor therapy 10 . Pancreatic and duodenal homeobox 1 (PDX1) shifts from a tumor-suppressive to an oncogenic function after tumor transformation 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The ImmuneScore and StromalScore of each LUAD patient were calculated using “estimate package”. A higher ImmuneScore or StromalScore indicates that more immune cells or stroma were expelled within tumor microenvironment (TME) 10 . Kaplan–Meier curves were plotted using the R survival package to predict the survival difference between low- and high-risk groups of LUAD patients.…”
Section: Methodsmentioning
confidence: 99%
“…Many current studies have focused on the effect of immune and ferroptosis-related gene expression on tumors [ 47 , 48 , 49 , 50 , 51 ]. The discovery of IFRGs could help to discover potential cancer targets.…”
Section: Discussionmentioning
confidence: 99%